Fragmented Stability: Recalls and Fixed-Term Contracts in the French Labour Market - Olivier Charlot; Franck Malherbet; Eloise Menestrier (Institute of Labor Economics (IZA), 2024)
This study investigates in a European perspective the phenomenon of recalls, in which previously laid off or furloughed employees are rehired by the same employer. It specifically examines the French labour market, notable for its pronounced degree of contractual dualism. A novel theoretical model is proposed, illustrating that recalls linked to fixed-term contracts contribute to employment fragmentation. Then, drawing on extensive linked employer-employee data from France spanning 2012 to 2019, we offer fresh empirical insights into recall practices. Our findings reveal a substantial recall rate of 44%, primarily involving fixed-term contracts of short duration, highlighting the strong link between recalls and contractual dualism. Contrary to expectations, recalls are prevalent even in sectors with stringent fixed-term contract regulations, suggesting potential lapses in enforcement. Our results suggest that a significant proportion of recalls could breach the legal requirements governing the use of fixed-term contracts. At a more granular level, over a quarter of recalled workers are rehired more than five times a year, with women and older employees disproportionately affected—further intensifying labour market segmentation. Firm-level analysis reveals a positive correlation between recalls and both firm size and productivity, while primarily attributing recall practices to fixed firm characteristics. This is observed both in the share of entries into recalled employment and in the duration of contracts upon recall. Overall, recalls may meet firms' structural needs, however, insufficient incentives to stabilise employment and weak regulatory enforcement contribute to increased employment fragmentation and labour market segmentation. Overall, the joint use of recalls and fixed-term contracts leads to a particular labour market dynamics that we term as fragmented stability.
Keywords: J21; J41; J42; J63; J64; J68; 330; fixed-term contracts; recalls; rehiring; employment protection legislation